The Role of NLRP3 and IL-1β in the Pathogenesis of Inflammatory Bowel Disease - Mao, Liming; Kitani, Atsushi; Strober, Warren; Fuss, Ivan J. (Frontiers in Immunology, 2018)
It is logical to assume that a major pro-inflammatory mechanism the NLRP3 inflammasome would play a prominent role in the pathogenesis of the Inflammatory Bowel Disease in humans. However, while both studies of murine models of gut disease and patients provide data that the main cytokine product generated by this inflammasome, IL-1B does in fact contribute to inflammation in Inflammatory Bowel Disease (IBD), there is no evidence that IL-1B plays a decisive or prominent role in “ordinary” patients with IBD (Crohn’s disease). On the other hand, there are several definable point mutations that result in over-active NLRP3 inflammasome activity and in these cases, the gut inflammation is driven by IL-1B and is treatable by biologic agents that block the effects of this cytokine.